Atezolizumab plus bevacizumab and chemotherapy in non-small-cell lung cancer (IMpower150): key subgroup analyses of patients with EGFR mutations or baseline liver metastases in a randomised, open-label phase 3 trial. Issue 5 (May 2019) - Reck, Martin; Mok, Tony S K; Nishio, Makoto; Jotte, Robert M; Cappuzzo, Federico; Orlandi, Francisco; Stroyakovskiy, Daniil; Nogami, Naoyuki; Rodríguez-Abreu, Delvys; Moro-Sibilot, Denis; Thomas, Christian A; Barlesi, Fabrice; et al.
Summary: Background: The IMpower150 trial showed significant improvements in progression-free and overall survival with atezolizumab plus bevacizumab plus carboplatin plus paclitaxel (ABCP) versus the standard-of-care bevacizumab plus carboplatin plus paclitaxel (BCP) in chemotherapy-naive patients with non-squamous non-small-cell lung cancer. Here, we report the efficacy of ABCP or atezolizumab plus carboplatin plus paclitaxel (ACP) versus BCP in key patient subgroups. Methods: IMpower150 was a randomised, open-label, phase 3 study done at 240 academic medical centres and community oncology practices across 26 countries worldwide. Patients with chemotherapy-naive metastatic non-small-cell lung cancer were randomly assigned (1:1:1) to receive ABCP, ACP, or BCP every three weeks. The co-primary endpoints were overall survival and investigator-assessed progression-free survival in intention-to-treat wild-type patients (patients with epidermal growth factor receptor [ EGFR ] or anaplastic lymphoma kinase [ ALK ] genetic alterations were excluded). Efficacy was assessed in key subgroups within the intention-to-treat population, including patients with EGFR mutations (both sensitising and non-sensitising; EGFR -positive) previously treated with one or more tyrosine kinase inhibitors and patients with baseline liver metastases. Overall survival in the intention-to-treat population was included among secondary efficacy endpoints. Exploratory endpoints included the proportion of patients achieving an objective response in the intention-to-treat population, including EGFR -positive patients and patients with baseline liver metastases. Data are reported as per the Jan 22, 2018, data cutoff date, at which the number of coprimary prespecified overall survival events was met in the ABCP versus BCP groups. This trial is registered with ClinicalTrials.gov, number NCT02366143, and is ongoing. Findings: Between March 31, 2015, and Dec 30, 2016, 1202 patients were enrolled. 400 patients were randomly assigned to ABCP, 402 to ACP, and 400 to BCP. In EGFR -positive patients (124 of 1202), median overall survival was not estimable (NE; 95% CI 17·0–NE) with ABCP (34 of 400) and 18·7 months (95% CI 13·4–NE) with BCP (45 of 400; hazard ratio [HR] 0·61 [95% CI 0·29–1·28]). Improved overall survival with ABCP versus BCP was observed in patients with sensitising EGFR mutations (median overall survival NE [95% CI NE–NE] with ABCP [26 of 400] vs 17·5 months [95% CI 11·7–NE] with BCP [32 of 400]; HR 0·31 [95% CI 0·11–0·83]) and in the intention-to-treat population (19·8 months [17·4–24·2] vs 14·9 months [13·4–17·1]; HR 0·76 [0·63–0·93]). Improved median overall survival with ABCP versus BCP was seen in patients with baseline liver metastases (13·3 months [11·6–NE] with ABCP [52 of 400] vs 9·4 months [7·9–11·7] with BCP [57 of 400]; HR 0·52 [0·33–0·82]). Median overall survival was 21·4 months (95% CI 13·8–NE) with ACP versus 18·7 months (95% CI 13·4–NE) with BCP in EGFR -positive patients (HR 0·93 [95% CI 0·51–1·68]). No overall survival benefit was seen with ACP versus BCP in patients with sensitising EGFR mutations (HR 0·90 [95% CI 0·47–1·74]), in the intention-to-treat population (HR 0·85 [0·71–1·03]), or in patients with baseline liver metastases (HR 0·87 [0·57–1·32]). In the intention-to-treat safety-evaluable population, grade 3–4 treatment-related events occurred in 223 (57%) patients in the ABCP group, in 172 (43%) in the ACP group, and in 191 (49%) in the BCP group; 11 (3%) grade 5 adverse events occurred in the ABCP group, as did four (1%) in the ACP group, and nine (2%) in the BCP group. Interpretation: Improved survival was noted for patients treated with ABCP compared with those given BCP in the intention-to-treat population, and in patients with baseline liver metastases. The overall survival signal in the subgroup of patients with EGFR sensitising mutations warrants further study. Funding: F. Hoffmann-La Roche, Genentech.